PENGARUH MEDIA SOSIAL TERHADAP PERILAKU SOSIAL SISWA MADRASAH IBTIDAIYAH MUHAMMADIYAH 11 BARA-BARAYA - Sri Hardianti; Nurfathunnisa; Amaliah Putri; A. Muhajir Nasir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of social media has influenced various aspects of life, including the social interactions of elementary school children. At Madrasah Ibtidaiyah Muhammadiyah 11 Bara-Baraya, students actively use social media, but its impact on their social behavior is not yet clear. The urgency of this research lies in the importance of understanding the role of social media as a communication tool and its effect on the development of students' social skills, which can serve as a basis for strategies in character building and digital literacy in schools. This study aims to analyze the influence of social media use on students' social behavior. The research employs a quantitative ex post facto approach with a population of all madrasah students and a purposive sample of 30 students. The instrument consists of a questionnaire with a 1–4 Likert scale, followed by non-participant observation to obtain supporting data. Data analysis was conducted through validity and reliability tests, classical assumption tests (normality, heteroscedasticity, multicollinearity), as well as simple linear regression analysis to examine the effect of social media use on students' social behavior. The results of the study indicate that both partially and simultaneously, social media use does not have a significant effect on students' social behavior. Social behavior is more influenced by contextual and environmental factors, such as face-to-face interactions with peers, teacher guidance, learning experiences, as well as family and school culture influences. These findings confirm that social media serves as a means of supporting interaction, but is not a primary factor in shaping students' social behavior.